The influence of exercise modality and intensity on ventricular arrhythmia burden and perception of effort in patients with Arrhythmogenic Right Ventricular Cardiomyopathy with plakophilin-2 variants - Fernando G. Beltrami; Kyle G. P. J. M. Boyle; Guan Fu; Corinna Brunckhorst; Firat Duru; Christina M. Spengler; Ardan M. Saguner (Current Issues in Sport Science)
Introduction Intense endurance exercise is discouraged for patients with arrhythmogenic right ventricular cardiomyopathy (ARVC), as it can increase the risk for adverse cardiac events as well as accelerate disease progression. While a sedentary lifestyle is also not advisable, there is currently no prospective data on the safety of physical activity for ARVC patients. To describe ARVC patients' average and peak ventricular arrhythmia burden – estimated from the prevalence of premature ventricular contractions (PVC) – measured during and after different exercise modalities and intensities, in context with cardiac and physiological load.